2018
DOI: 10.1002/1873-3468.13096
|View full text |Cite
|
Sign up to set email alerts
|

A novel amyloid designable scaffold and potential inhibitor inspired by GAIIG of amyloid beta and the HIV‐1 V3 loop

Abstract: The GAIIG sequence, common to the amyloid beta peptide (residues 29-33) and to the HIV-1 gp120 (residues 24-28 in a typical V3 loop), self-assembles into amyloid fibrils, as suggested by theory and the experiments presented here. The longer YATGAIIGNII sequence from the V3 loop also self-assembles into amyloid fibrils, of which the first three and the last two residues are outside the amyloid GAIIG core. We postulate that this sequence, with suitably selected modifications at the flexible positions, can serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(64 citation statements)
references
References 69 publications
1
63
0
Order By: Relevance
“…In the second approach, we aimed to rationally design a functional amyloid peptide with cell-penetrating and DNA-binding properties using the amyloid designable scaffold, YATGAIIGNII [31], as a basis. As, according to our previous study [31], residue positions one, two, three, and eleven are amenable for modification as they are not part of the β-sheet core, we rationally designed peptide sequences by introducing mutations to the designable (underlined) positions of YATGAIIGNII. Similarly to the rational design described above, we performed a bioinformatics analysis for sequence motifs containing positively charged residues or tyrosines within cell-penetrating peptides deposited in CPPsite2.0 [40].…”
Section: Rational and Computational Design Of The Positively Charged mentioning
confidence: 99%
See 2 more Smart Citations
“…In the second approach, we aimed to rationally design a functional amyloid peptide with cell-penetrating and DNA-binding properties using the amyloid designable scaffold, YATGAIIGNII [31], as a basis. As, according to our previous study [31], residue positions one, two, three, and eleven are amenable for modification as they are not part of the β-sheet core, we rationally designed peptide sequences by introducing mutations to the designable (underlined) positions of YATGAIIGNII. Similarly to the rational design described above, we performed a bioinformatics analysis for sequence motifs containing positively charged residues or tyrosines within cell-penetrating peptides deposited in CPPsite2.0 [40].…”
Section: Rational and Computational Design Of The Positively Charged mentioning
confidence: 99%
“…Amyloid formation was thought to be associated solely with amyloid diseases such as Alzheimer's and Parkinson's diseases [23][24][25][26]. However, numerous studies demonstrated that amyloids could also be exploited as promising bionanomaterials [27,28] or even assume physiologically relevant roles [29,30].We previously demonstrated that the ultrashort and homologous peptide sequences GAITIG and GAIIG can spontaneously self-assemble into amyloid fibrils [31,32]. The GAITIG sequence is part of the adenovirus fiber shaft segment that, in the absence of its natural trimerization motif, aggregates into amyloid-type fibrils.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure of the Asn1 (N) and Ser2 (S) residues makes them accessible and thus amenable to modifications. Moreover, we recently proved theoretically and experimentally, that the homologous sequence GAIIG which corresponds to residues 29–33 of the amyloid beta peptide and to the V3 loop of the HIV gp 120 (residues 24–28 in a typical V3 loop sequence) self‐assembles into amyloid fibrils . The longer YATGAIIGNII sequence of the V3 loop also self‐assembles into fibrils of which the N‐terminal YAT and C‐terminal II residues are exposed outside the fibril core and therefore amenable to modifications; therefore GAIIG is also a key beta sheet determinant (see below).…”
Section: Natural Fibrous Assemblies As a Source Of Inspiration For Tementioning
confidence: 99%
“…According to our computational protocol strategy, the amyloid scaffold GAIIG which derives from the amyloid forming sequences of Aβ peptide and the V3 loop of HIV‐1 gp120, was used as the beta sheet core and was functionalized to bind a specific ion by introducing mutations at the C‐ and N‐termini; these areas are amenable to modifications since they do not participate in the beta sheet core formation. The peptide AGKGAIIGFIK was used as the initial scaffold used with GK and IK serving as mutable positions.…”
Section: Computational Design Of Functional Amyloid Materials Bindingmentioning
confidence: 99%